Effect of organic acid on phosphorus-use efficiency by clusterbean (Cyamopsis tetragonoloba) in arid soil of Rajasthan - Tripathi, K P (The Indian Journal of Agricultural Sciences, 2005)
A field experiment was conducted during 1999-2000 with 3 levels of P applied through diammonium phosphate (0,30 and 60 kg P2O5/ha) along with 3 levels of acetic acid (0,0.2 and 2.0 mM) to find out the effect of weak organic acid on mobilization of native and applied P in soil and P uptake by clusterbean [Cyamposis tetragonoloba (L.) Taubert]. There was no effect of acetic acid application on the Olsen-P in soil. Phosphorus buffering capacity of soil was unaffected at 0.2 mM acetic acid, however it significantly increased by 2 mM acetic acid application. Similarly, P content in the leaves of clusterbean significantly increased with 2.0 mM application of acetic acid. It was further observed that total P uptake of crop with 2.0 mM of acetic acid and 30.0 kg P2O5/ha treatment was equally effective with the application of 60 kg P205/ha. This indicated increased P availability to crop in presence of acetic acid applied along with fertilizer P.